Estimation of Fertility due to Contraception in Nepal - Devkota, Bijaya Mani (Journal of Business and Social Sciences Research, 2018)
Fertility has an important role for demographic transition and total fertility rate (TFR) which is one component measurements of fertility. Absences of complete and reliable data, a large number of indirect techniques have been developed to estimate demographic parameters. Some of these techniques are based on stable population theory and others are regression equations between the dependent variables, the TFR and the independent variables, the socio economic as well as demographic variables. The unwanted or unintended pregnancies can be avoided through the use of contraceptives; it becomes very important to estimate the births averted or pregnancies stopped by use of contraception. Though there is increase in the use of contraception, still many couples do not use contraception in spite of the fact that they require to use contraception. To satisfy this unmet need of contraception is one of the policy targets of national population policy for population stabilization. In this study, 12862 married females between 15-49 years of age, whose marital duration is more than 5 years, have been taken to study the distribution on different background characteristics and their behavior. Firstly, a regression study was done to know the impact on contraceptive use and further multivariate study has been carried out to know the effect of background characteristics and behavior on absence of birth five years jointly at different sub division. This method is based on the relationship between the Total fertility rate (TFR) and contraceptive prevalence rate (CPR).By using this modified estimate of TFR, birth averted for different area. The variables are CPR that about 71.4 percent variation in TFR can be explained by the first regression approach. The second is based on the relationship between total fertility rate (TFR) and Additive combination of CPR and proportion of currently married females having open birth interval (NPV) explained about 82percent of the variation in TFR. The findings revealed that the TFR calculated by the present method are quite close to the observed values of the TFR. Estimates of births averted and the percent change in births in the absence of contraception, based on the two methods are fairly consistent.